ANALISIS PENGARUH INFORMASI LAPORAN KEUANGAN TERHADAP PERUBAHAN HARGA SAHAM SEBELUM DAN SELAMA KRISIS EKONOMI INDONESIA (STUDI KASUS PERUSAHAAN G0 PUBLIK DI BEJ) - Irwan Mangara Harahap (Universitas Mercu Buana, 2015)
This study examined the effect of financial statement information on stock price movements on the companywent public on the JSE. Financial statement information represented financial ratios commonly used in capitalmarkets that is Earnings Per Share (EPS), Price EarningRatio (PER), Price to Book Value (PBV), Debt to EquityRatio (DER), Return On Investment (ROI) , Return On Equity (ROE) and Profit Margin (PM). Economic crisis isused as the cut-off study due to previous research by many companies in Indonesia affected either directly orindirectly so that there is a significant difference between the period before the 'economic crisis and during theeconomic crisis. The population in this study is the go-public company listed on the Jakarta Stock Exchange in 1995-1999. The number of companies registered during the period amounted to 204 companies from variousindustries. The research sample also uses the company from all types of industries and using purposivesampling method and the number of population after selected according to the criteria obtained a sample of104 companiesThe research data is secondary data obtained from PRPM Jakarta, Semarang PIPM, JSX CornerDiponegoro, Indonesia Capital Market Directory and Internet (Indoexchange.com and jsx.co. id) The resultsshow that by using the level of a -. 5% variable EPS, PBV significantly in the period before and during the crisis.DER variable sigmifikan only in the period before the 'crisis. Variable ROI and ROE significant only in the periodbefore the crisis, while the PER and the PM variable is not significant at all periods. Taken together well in theperiod before and during the crisis of financial ratio variables (independent variables) influence sigmifikan tovariable changes in stock prices (the dependent variable). Economic crisis also significantly differentiate theeffect between the period before of during the economic crisis.